Integrating Interface Design and Usability Evaluation in a Web-Based Zakat and Sadaqah Application - Khasanah, Fata Nidaul (Program Studi Teknik Komputer, 2026)
Purpose – This study aims to design a user-centered interface for a web-based E-Zakat application to support the digital management of zakat and sadaqah by Mosque Prosperity Councils in the Industry 5.0 era. Design/methods/approach – The research adopts a user-centered design approach in developing the application interface. A usability evaluation was conducted using the Heuristic Evaluation method to assess the effectiveness, efficiency, and user experience of the designed interface. Findings – The results show that 80% of the interface design elements did not present any usability issues. However, two indicators were identified as cosmetic problems, indicating minor improvements are needed in future iterations. Research implications/limitations – This study is limited to interface design and usability evaluation using heuristic methods, without involving extensive user testing. Future research can expand by incorporating empirical user testing and system implementation to validate real-world effectiveness. Originality/value – This study contributes to the digital transformation of mosque financial management by providing a user-centered interface design specifically for E-Zakat systems, enhancing transparency, efficiency, and accessibility in managing zakat and sadaqah.